Family Language Policy within Nubian Families in Egypt: Parents’ Perspectives of Their Children’s Prospective Bilingualism - Ahmed, Radwa Ezzat (AUC Knowledge Fountain, 2021)
Abstract This study attempts to investigate the main features of family language policy (FLP) within Nubian families in Egypt in relation to the maintenance of the Nubian language. Further examination of the relationship between the major demographic characteristics of Nubian parents and the FLP they follow with their children is pursued along with an exploration of the role contextual factors play in FLP within these Nubian families. To this end, the study employed a mixed methodological approach for data collection starting with employing an online questionnaire and terminating with conducting a number of follow-up semi-structured interviews with a selected group from the questionnaire participants. One hundred and twenty participants took part in the questionnaire, and 11 of them participated in the follow-up interviews. Findings of this study show that the FLP applied by the Nubian parents with their children was influenced by a complex web of connections including the demographic characteristics of Nubian parents and some contextual factors that have played an important role in shaping the language profiles of these families. In terms of the demographic characteristics, the results have revealed that there is a positive correlation between the parental age and the parental language proficiency in Nubian and the FLP supporting the maintenance of the Nubian language, while there is an inverse correlation between the parental education and the FLP supporting the maintenance of the Nubian language. As for the contextual factors, it has been found that there is an inverse correlation between socioeconomic background and the acculturation of the parents on one hand, and the FLP supporting the maintenance of the Nubian language on the other hand. Also, the results have shown that there is no significant relationship between the family structure as one of the contextual factors and the FLP supporting the maintenance of the Nubian language.